2016
DOI: 10.1007/s11099-016-0207-9
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of leaf traits with changing source-sink relationship in blueberry (Vaccinium corymbosum L.) leaves

Abstract: The source-sink relationship is one of major determinants of plant performance. The influence of reproductive sink demand on light-saturated photosynthesis (P (max)), dark respiration (R (D)), stomatal conductance (g (s)), intrinsic water-use efficiency (WUEi), contents of soluble sugar (SSC), nitrogen, carbon, and photosynthetic pigments was examined in blueberry (Vaccinium corymbosum L. cv. 'Brigitta') during the final stage of rapid fruit growth. Measurements were performed three times per day on developed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…3). In this sense, as evidenced by Jorquera-Fontena et al (2016) in Brigitta blueberries, it is possible that the elimination of strong sink organs such as flowers and/or berries in our experiment induced a limitation in the maximum expression of photosynthesis. However, studies conducted by Fan et al (2010) and Nebauer et al (2011) on apple and citrus, respectively, reported that the roots of young plants can exert a demand for sugars similar to fruits.…”
mentioning
confidence: 78%
“…3). In this sense, as evidenced by Jorquera-Fontena et al (2016) in Brigitta blueberries, it is possible that the elimination of strong sink organs such as flowers and/or berries in our experiment induced a limitation in the maximum expression of photosynthesis. However, studies conducted by Fan et al (2010) and Nebauer et al (2011) on apple and citrus, respectively, reported that the roots of young plants can exert a demand for sugars similar to fruits.…”
mentioning
confidence: 78%
“…According to Latsague et al (2014), the photosynthetic capacity of leaves is related to the N content, because an adequate supplement of N is essential in the establishment of maximum demand capacity and photosynthetic capacity; but excessive use of N causes excessive expansion of the foliar area. Jorquera-Fontena et al (2016) observed that the accumulation of photosynthetic pigments in blueberry plants is an indicator of biomass production and the nutritional status of N. According to most of the research done, the ratio of chlorophyll a and b is 3:1, which varies depending on plant growth and development, cultivar, and environmental factors (Bojovic and Stojanovic, 2005). Sánchez et al (2018) obtained a positive and significant correlation of the concentration of chlorophyll a, chlorophyll b and carotenoids with the nutritional state of N, in bean (Phaseolus vulgaris L.).…”
Section: Effect Of N Form and Split Roots On Photosynthetic Pigmentsmentioning
confidence: 99%
“…Pereira et al found that trunk girdling applied at veraison, in "Cabernet Sauvignon" wine grapes (Vitis vinifera L.) increased anthocyanin and flavonol concentrations in skin/pulp tissues of grape berries without affecting primary metabolites. Trunk girdling trials might be applied to change the source-sink relationship on blueberry as already reported by Jorquera-Fontena et al (2016). Zuñiga et al demonstrated that increasing the number of methyl jasmonate preharvest applications (maximum three treatments) on strawberry (Fragaria ananassa "Camarosa") improved the anthocyanin, proanthocyanidin, and ascorbic acid content of the fruit, as well as the antioxidant-related enzymatic activity during postharvest storage.…”
mentioning
confidence: 91%
“…found that trunk girdling applied at veraison, in “Cabernet Sauvignon” wine grapes ( Vitis vinifera L.) increased anthocyanin and flavonol concentrations in skin/pulp tissues of grape berries without affecting primary metabolites. Trunk girdling trials might be applied to change the source-sink relationship on blueberry as already reported by Jorquera-Fontena et al. (2016) .…”
mentioning
confidence: 97%